Periodontal conditions in patients with coronary heart disease: a case–control study - Carin Starkhammar Johansson (Blackwell Synergy, 2008)
Aim: This study examined periodontal conditions in patients with coronary heart disease (CHD) and subjects with no history of CHD. Material and Methods: Participants were 161 patients (40–75) with severe angina pectoris (diagnosed as CHD by coronary angiography) who subsequently underwent percutaneous coronary intervention and 162 control subjects with no history of CHD. Periodontal status was recorded. Bone loss was determined on radiographs. Periodontal disease experience was classified into five groups according to Hugoson & Jordan. Results: Periodontal disease experience groups 4 and 5 were more common in the CHD group (25%) compared with the control group (8%). The mean bone level (the distance from the CEJ to the most coronal level of the alveolar bone) was 3.0 1.0mm in CHD subjects and 2.6 0.8mm in controls. CHD patients had significantly lower numbers of natural teeth, higher numbers of periodontal pockets 4–6-mm and higher bleeding on probing (%). In a stepwise regression analysis, the factor periodontal disease experience groups 415 gave an odds ratio of 5.74 (2.07– 15.90) for having CHD after controlling for smoking and age. Conclusion: Severe periodontal disease expressed by several clinical and radiographic parameters was more prevalent among subjects with CHD than among controls. Analysis, the factor periodontal disease experience groups 415 gave an odds ratio of 5.74 (2.07–15.90) for having CHD after controlling for smoking and age.